In-situ study the low-cycle fatigue deformation behavior of a fourth-generation nickel-based single crystal superalloy at 1100 °C - Yongfeng Wang; Wenqiang Zhang; Jutian Chen; Shuang Chen; Junxia Lu; Yuefei Zhang; Ze Zhang (Journal of Materials Research and Technology)
An in-situ fatigue testing device, equipped in scanning electron microscope (SEM) and designed for long-time high temperature and complex stress testing conditions, was developed. The fatigue crack initiation and propagation behavior of notched Nickel-based single crystal superalloy (Ni-SX) was studied using the fatigue device combined with optimized speckle preparation. The mechanisms of crack initiation and propagation were analyzed using digital image correlation (DIC) and crystal plasticity finite element (CPFE) analysis. The results showed that fatigue crack initially formed at the notch root and propagated in mode II under the influence of the local stress distribution. As the stress field changed with fatigue, the crack propagation transitioned into a mixed mode. The micro in-situ high-temperature fatigue device and methodology are essential for studying low-cycle fatigue and local stress distribution in superalloys, especially under high-temperature conditions.